Farm-related determinants of food insecurity among livestock dependent households in two agrarian districts with varying rainfall patterns in Ghana - Nuvey, Francis Sena; Nortey, Priscillia Awo; Addo, Kennedy Kwasi; Addo-Lartey, Adolphina; Kreppel, Katharina; Houngbedji, Clarisse Abikpo; Dzansi, Gladys; Bonfoh, Bassirou (Frontiers in Sustainable Food Systems, 2022)
Background Despite availability of sufficient arable land, many African countries continue to dawdle in agricultural productivity due to over-reliance on rainfall patterns. Thus, undernourishment levels are disproportionately high in Africa. Even though they play key roles in agricultural production, the food security (FS) levels of livestock dependent households are understudied. Our study assessed the FS level and its determinants in livestock farming households in Ghana. Methods We compared the FS levels of 287 cattle producing households in two representative agrarian districts with varying rainfall patterns in Ghana (dry vs. wet), using a cross-sectional survey. We assessed household's FS using the Food Insecurity Experience Scale. FS scores and categories were computed, and using generalized linear models, we assessed factors that explained variations in the FS levels among households. Results The median herd size of households was 31 cattle (lower quartile = 24, upper quartile = 60 cattle), with a majority (91%) engaged in crop cultivation. Households reported experiencing an average of eight adverse events over a five-year recall period (2014–2018) mainly from animal diseases, cattle theft, and pasture shortages. Most households (81%) were food insecure (moderate = 40%, severe = 41%). In an adjusted model, households raising cattle in the dry district [adjusted Odds Ratio (aOR) = 5.43, 95% CI: 1.94, 15.2] and being married (aOR = 9.48, 95% CI: 2.35, 38.3) were associated with moderate food insecurity. While households raising cattle in the dry district [adjusted Odds Ratio (aOR) = 4.17, 95% CI: 1.44, 12.0], being married (aOR = 3.55, 95% CI: 1.03, 12.2), and increase in number of adverse events experienced (aOR = 1.53, 95% CI: 1.20, 1.96), were associated with increased odds of severe food insecurity. Household's odds of severe food insecurity decreased with each additional head of cattle in their herds (aOR = 0.97, 95% CI: 0.96, 0.99). We find no evidence of effect modification by farming district on other predictor's effect on food insecurity. Conclusion Most of the livestock dependent households are food insecure. The food insecurity levels are worse for households farming in dry areas, those married and who experience increased frequency of adverse events. Government policy interventions focusing on maintaining healthy, secure, and productive animal herds would contribute to improving the productivity of household herds, food safety and food security.